Tree species diversity in secondary forest of Mount Pangasugan, Baybay City, Philippines - Polinar, Anatolio Narollo; Muus, Uwe (2010)
The study was conducted to determine the species diversity and similarities of a two hectare secondary forest located at the foothills of Mount Pangasinan and within the forest reservation of Visayas State University.